Study of the Effect of Green Investment Policy, Technological Innovation, and Sustainable Development on Industrial Competitiveness - Hendri Khuan; Loso Judijanto; Nekky Rahmiyati; Ramdan Yusuf; Tungga Bhimadi Karyasa (West Science Interdisciplinary Studies, 2024)
This research investigates the intricate relationships among green investment policy, technological innovation, sustainable development, and industrial competitiveness within the context of Indonesia. Employing a quantitative research design, data were collected from a stratified random sample of 110 participants representing diverse industries. Descriptive statistics, correlation analysis, regression analysis, and structural equation modeling were utilized for analysis. The results revealed positive correlations and significant coefficients, indicating the individual and combined contributions of green investment policy, technological innovation, and sustainable development to industrial competitiveness. The findings underscore the importance of a holistic approach to sustainability for enhancing the competitiveness of Indonesian industries.